Analysis of factors influencing career preparation behaviors of Korean student athletes according to regional context - Ha, Seong Jun (Frontiers in Psychology, 2025)
This study analyzed the effects of social support and school adjustment on career preparation behaviors among Korean high school soccer players and empirically examined the moderating effect of region (metropolitan/non-metropolitan) on the relationship between these variables. To achieve this, a survey was conducted on 223 male high school football players from six high schools located in the Seoul metropolitan area and non-metropolitan areas. The relationships among school life adjustment, social support, and career preparation behaviors were analyzed using SPSS 27 and Process Macro 4.0 (Model 15). The results showed that both social support and school adjustment had a significant positive influence on career preparation behaviors, and the relationship between these variables was moderated by region. Specifically, social support directly influenced career preparation behaviors in the Seoul National Capital Area, but in the non-Seoul National Capital Area, it exerted an indirect influence through school adjustment. On the other hand, the influence of school life adjustment was relatively stronger in non-metropolitan areas. These results suggest that regional educational disparities structurally influence the career formation process of student athletes and emphasize the need for region-specific career support strategies.